An Econometric Analysis on the Co-Movement of Stock Market Volatility between China and ASEAN-5 - Jakpar, S.; Vejayon, V.; Johari, Anita; Myint, Khin (Centre for Promoting Ideas, 2013)
This study aims to examine the co-movement of stock market volatility between China and ASEAN-5 countries from the year 2000 to 2009. This study applies the standard linear GARCH (1, 1) model where these models estimate using monthly price data from year 2000 to 2009 for China, Malaysia, Singapore, Thailand, Indonesia and Philippines. The standard time series econometrics analysis is used which are ADF unit root test, JJ co-integration test, and Granger causality test. The results indicate the co movement of stock market volatility between China and ASEAN-5 have fairly relation among them. The result shows there are two way relations which are bidirectional causality between china and Indonesia; China and Thailand; and China and Singapore. Meanwhile, there have no causality relation between China and Malaysia; and also China and Philippines. Though, it can be concluded that there are relationship between regions in the stock market volatility.